2017
DOI: 10.1039/c7nr03747c
|View full text |Cite
|
Sign up to set email alerts
|

Phonon-glass electron-crystals in ZnO-multiwalled carbon nanotube nanocomposites

Abstract: We propose a strategy for enhancing thermoelectric performance through the realization of a 'phonon-glass electron-crystal' (PGEC) by interface control using multiwalled carbon nanotubes (MWCNTs). By the consolidation of undoped ZnO nanoparticles with MWCNTs (0.5, 1, and 2 wt%) using spark plasma sintering, we fabricated the interface-controlled ZnO-MWCNT nanocomposites, in which ZnO grains were surrounded with a MWCNT network. Both single crystal-like charge transport (electron-crystal) and considerably reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…solved the problem by introducing coherent phonon scattering into the field. They hypothesized diffraction to be the source of scattering, which adequately explains the decrease of lattice thermal conductivity of other coated grain structures. To verify their hypothesis, they also synthesized a coated grain structure. The coating of CdTe on SnTe was accomplished on the basis of cation-exchange technique, a method used for core/shell nanoparticles .…”
Section: Extrinsic Scattering: Nanoparticles Nanosized Grains Coated ...mentioning
confidence: 99%
See 1 more Smart Citation
“…solved the problem by introducing coherent phonon scattering into the field. They hypothesized diffraction to be the source of scattering, which adequately explains the decrease of lattice thermal conductivity of other coated grain structures. To verify their hypothesis, they also synthesized a coated grain structure. The coating of CdTe on SnTe was accomplished on the basis of cation-exchange technique, a method used for core/shell nanoparticles .…”
Section: Extrinsic Scattering: Nanoparticles Nanosized Grains Coated ...mentioning
confidence: 99%
“…on the same material, both studies revealed a reduction in thermal conductivity. To add, reduction in thermal conductivity was also evident in other coated grain structures. Although people did observe a reduction in thermal conductivities based on a coated grain structure, the exact reason for such reduction was not known since the grain size was rather large, a few μm or 10 μm in size. It was widely known that a large interfacial area per unit volume was required to scatter phonons effectively.…”
Section: Extrinsic Scattering: Nanoparticles Nanosized Grains Coated ...mentioning
confidence: 99%
“…According to our developed theory, our coated grains offer much larger phonon-scattering cross sections compared to those of nanodots nanocomposites. The theory successfully explains lattice thermal conductivity of other coated grain structures. Also, this structure is beneficial for electron transport because (i) electron-impurity scattering can be reduced based on wider interimpurity distances inside the grains ( i.e. , intercoating distance) and (ii) the electron-filtering effect can occur on the basis of the heterostructure barriers created by the coated layers to further enhance the power factor …”
mentioning
confidence: 96%
“…(A) Carrier concentration; (B) Carrier mobility; (C) Density of states effective mass; (D) Calculated Pisarenko plots with different effective mass m d * and experimental results from this work and other reported literature 10,24‐27 in ZnO‐based thermoelectric materials [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Resultsmentioning
confidence: 88%